Can thiệp của chính phủ, đổi mới công nghệ xanh và tiêu thụ năng lượng tái tạo: Bằng chứng tại Việt Nam - Ngô Thái, Hưng; Nguyễn Khánh, An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The 2015 Paris Agreement highlights global commitments to reduce greenhouse gas emissions and strengthen climate change response efforts. In this context, renewable energy development is widely recognized as a key pathway to achieving climate goals, with government intervention and green technological innovation playing important facilitating roles. Therefore, this study aims to measure the linkages between GOV–REN and TEC–REN. Based on the Wavelet Local Multiple Correlation (WLMC) method, the results indicate that government intervention exerts a positive correlation on renewable energy consumption in the short term but a negative correlation in the long term. In contrast, green technological innovation shows a consistently positive correlation with renewable energy consumption across both short- and long-term horizons. In addition, the impact of economic growth (GDP) on the linkages between GOV–REN and TEC–REN is also examined. The results highlight that the relationship between GDP and REN is determined by GOV and TEC across different time periods and frequencies. These findings have important implications for strengthening policies to achieve energy development and sustainable economic growth.